Conundrums in the surgical intensive care unit: fevers and antibiotic prophylaxis - Niels D Martin; Diane N Haddad; Patricia Martinez Quinones; Sriharsha Gummadi (Trauma Surgery & Acute Care Open)
This editorial is in response to the three latest clinical consensus guidelines authored by the Critical Care Committee of the American Association for the Surgery of Trauma. Herein, we discuss their main findings and recommendations and their impact on the practice of Surgical Critical Care.